Exchange protein activated by cyclic AMP is involved in the regulation of adipogenic genes during 3T3-L1 fibroblasts differentiation - Gabrielli, Matias (2014)
Adipogenesis is stimulated in 3T3-L1 fibroblasts by a combination of insulin, dexamethasone and isobutylmethylxanthine, IBMX, (I+D+M). Two transcription factors are important for the acquisition of the adipocyte phenotype, C/EBP beta (CCAT enhancer-binding protein beta) and PPAR gamma (peroxisome proliferator-activated receptor gamma). IBMX increases cAMP content, which can activate protein kinase A (PKA) and/or EPAC (exchange protein activated by cAMP). To investigate the importance of IBMX in the differentiation mixture, we first evaluated the effect of the addition of IBMX on the increase of C/EBP beta and PPAR gamma and found an enhancement of the amount of both proteins. IBMX addition (I+D+M) or its replacement with a cAMP analogue, dibutyryl-cAMP or 8-(4-chlorophenylthio)-2-O′-methyl-cAMP (8CPT-2-Me-cAMP), the latter activates EPAC and not PKA, remarkably increased PPAR gamma mRNA. However, neither I+D nor any of the inducers alone, increased PPAR gamma mRNA to a similar extent, suggesting the importance of the presence of both IBMX and I+D. It was also found that the addition of IBMX or 8CPT-2-Me-cAMP was able to increase the content of C/EBP beta with respect to I+D. In agreement with these findings, a microarray analysis showed that the presence of either 8CPT-2-Me-cAMP or IBMX in the differentiation mixture was able to upregulate PPAR gamma and PPAR gamma-activated genes as well as other genes involved in lipid metabolism. Our results prove the involvement of IBMX-cAMP-EPAC in the regulation of adipogenic genes during differentiation of 3T3-L1 fibroblasts and therfore contributes to elucidate the role of cyclic AMP in this process.